Effect of Humor Therapy on Chronic Pain: A Literature Review - Yusnaeni, Yusnaeni; Erika, Kadek Ayu; Rachmawaty, Rini (Journal Of Nursing Practice, 2019)
Introduction: Chronic pain is an unpleasant sensory and emotional experience with actual or potential tissue damage, or is described as a damage lasting more than 3 months with heavy or moderate intensity. The patient's response to the pain he experienced was done in different ways such as shouting, grimacing, crying, etc. Repair of pain is likely to occur more quickly when psychological intervention is included in medical care because it requires alternative and complementary treatment to overcome the pain including prayer , humor, hypnosis, and group support. Growing evidence-based nursing practice shows progress in helping patients deal with the pain. One of the evidence-based nursing practices is humor therapy. Method: The literature search was done through searching the results of scientific publications 2010-2018 using several databases, such as Such as Google scholar, PubMed, DOAJ, and Cochran, with keyword "Humor Therapy and Chronic Pain. Result: Obtained 6 fulltext articles, were obtained with various methods used, such as quasi-experimental pre- and posttest control group design, randomized two-group review literature, concluded that humor therapy proved effective in reducing chronic pain in all ages. Conclusion: The humor therapy is effective in reducing chronic pain in patients of all ages, both children, adults and the elderly, besides humor therapy can also be used to increase endurance and quality of life in elderly who are cared for in nursing homes